A mobile social network for efficient contents sharing and searches. (January 2015) - Li, He; Bok, Kyoungsoo; Yoo, Jaesoo
Abstract: In this paper, we focus on constructing a mobile social network over a mobile ad hoc network. Although some mobile social networks have been proposed to address contents sharing and search in mobile ad hoc networks, most existing methods incur either high network management overheads or low efficiency of contents search. The proposed method constructs a mobile social network according to user interests and location information. Since the mobile nodes with nearby positions are linked together, the network management overhead of the proposed method is decreased. The contents search can be performed by using the constructed social links with low communication cost and high success rate. The various experimental results based on the synthetic datasets and real datasets have showed that the proposed method has a great advantage comparing to existing methods.